CULTURAL AND TOURISM DIVERSITY ON INSTAGRAM ACCOUNT OF BANDUNG CULTURAL AND TOURISM BOARD: A DISCOURSE ANALYSIS APPROACH - Rosaria Mita Amalia (National Conference on Applied Business, Education, & Technology (NCABET), 2021)
Cultural diversity is one of the nation's wealth that can be a tourist attraction in an area. The city of Bandung as the capital city of West Java Province has the potential and allure of tourism so that it can attract tourists to come. The Bandung City Tourism Culture Office is one of the offices that maximizes their official Instagram account @ disbudpar.bdg as a medium for promoting various tourist attractions and cultural diversity as one of the attractions of Bandung for tourists. The promotional content displayed in the Instagram account feeds represents the cultural and tourism diversity of Bandung city. Various potentials and cultural attractions are displayed in visual images and captivating narratives. The previous studies focuses on the potential value of Instagram for promoting tourism site in Indonesia, especially in Malang and Bali, and describing how Instagram creating brand destination through photography side.This study analyzes the topics presented and the linguistic instruments used as markers of cultural diversity and tourism in these contents. The analysis uses Fairclough's Critical Discourse Analysis (1995) theory regarding text analysis and the research method is descriptive quantitative. Topics that are displayed such as tourist attractions, art attractions, the use of Sundanese language, culinary tours, etc. show the various cultures and arts from the city of Bandung. The results of the analysis show that there are 11 classification of topics regarding cultural diversity and tourism namely